Association of female reproductive factor with risk of arthritis: a population-based cross-sectional study - Jiajia Wang; Yiting Ge; Jingbo Xu; Lin He; Chunjiang Liu; Yuefei Wang (Reproductive Health)
Abstract Background The purpose of the present study was to examine the association of female reproductive factor, including age at first birth (AFB), age at last birth (ALB), number of pregnancies, and live births with prevalence of arthritis in the female population of the American. Methods The present study analyzed cross-sectional data from a sample of females of National Health and Nutrition Examination Survey (NHANES) years 1999 through 2018. After adjusting for potential confounding factors, we used weighted multivariable logistic regression analysis, restricted cubic spline (RCS) model, and subgroup analysis to evaluate the association of AFB, ALB, number of live births, and pregnancies with prevalence of arthritis. Results A total of 15,842 female individuals were included in our analysis. The RCS showed that the U-shaped were found between AFB, and number of pregnancies with prevalence of arthritis. The above U-shaped correlation was also found for AFB and osteoarthritis (OA), rheumatoid arthritis (RA), and other arthritis, for ALB and OA. Among, number of pregnancies and OA, and RA were associated in a J-shape. However, ALB, and number of live births is negatively correlated with prevalence of arthritis. In addition, the association of ALB with OA, and other type arthritis, number of pregnancies with other arthritis, number of live births with RA, and other type arthritis showed linear negative correlation. In contrast, a positive linear correlation existed between number of live births and RA. Conclusions This study provides evidence that women with younger or later AFB have higher odds of arthritis (OA and RA) in later life. When screening for arthritis and devising preventive strategies, reproductive factors need to be taken into consideration.